2022
DOI: 10.1088/1741-4326/ac3a1c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recycling neutral on density shoulder formation in tokamak plasmas

Abstract: Towards the physical understanding on the formation of flattened upstream scrape-off-layer (SOL) density profiles, namely ‘density shoulders’, a self-consistent one-dimensional radial transport model has been developed to estimate the upstream profiles covering both core plasma and SOL region at tokamak midplane. For the SOL region, the effective density and temperature profiles for the ionization process are obtained by weighted averaging of the upstream and downstream profiles, which can distinguish the open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 70 publications
(127 reference statements)
1
6
0
Order By: Relevance
“…x and L D + y represent the contributions to the loss of D + particles by poloidal and radial transport, respectively, and V reg is the volume of the selected region. The negative value of L represents a net loss of particles from the region, and is consistent with the convention established in [12]. The total loss of D + source, L D+ SOL , is equal to the source provided by the plasma-neutral interactions.…”
Section: The Influence Of E × B Drift In Forward B T On Density Shoul...supporting
confidence: 74%
See 4 more Smart Citations
“…x and L D + y represent the contributions to the loss of D + particles by poloidal and radial transport, respectively, and V reg is the volume of the selected region. The negative value of L represents a net loss of particles from the region, and is consistent with the convention established in [12]. The total loss of D + source, L D+ SOL , is equal to the source provided by the plasma-neutral interactions.…”
Section: The Influence Of E × B Drift In Forward B T On Density Shoul...supporting
confidence: 74%
“…Meanwhile, the enhanced ion sources increase the local plasma density to feed the shoulder [19] when n D+,CEI is high. However, it has been reported that the 'density shoulder is caused by the competition between SOL particle loss term L SOL and effective ionization source term' [12]. L SOL depends strongly on particle transport, which is influenced significantly by E × B drift.…”
Section: Modelling Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations